Water pollution monitoring and management: a review of Bangkok - Ali, G.; Nitivattananon, V.; Ahmad, Waqas; Nawaz, R. (2010)
An increasing amount of scientific information is available on water pollution and its effect. Water pollution management for pollution control seldom considers the scientific information. The main objective of this paper is to review the water pollution management in Bangkok and link the entire process to the cause and effects of water pollution. Existing approaches for water pollution control primarily focuses on enforcing various standards. Respective local authorities in Bangkok have also set their own surface water quality requirement. However, the entire management approach requires further analysis in line with the present situation. This paper attempts to review the entire management approach and suggests reduction strategies, control measures/treatment systems and some preferred solutions to the water pollution management. It also covers other important measures for control. The conclusion proposes some policy recommendations on reducing pollution through effect management approach.